Activitie of polyphenoloxidase in yellow and purple onion - Calado, Joeliton Alves; Costa, Franciscleudo Bezerra; Pereira, Manoel Mykéias Duarte; Silva, Bruna Rocha; Sousa, Sabrina Vieira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The high perishability of the onion may limit the shelf life of the bulbs, mainly by the biochemical transformations. The objective of this work is to determine and compare polyphenoloxidase activity (PPO) in yellow and purple onions and their functional body. The raw material was purchased in the local market , where they were transported to the Food Analysis Laboratory of the, Center for Agro-Food Science and Technology, Federal University of Campina Grande, Campus Pombal, being selected, cleaned, sorted, peeled processed and carried out chemical and physico- chemical analysis and determination of the enzymatic activity of polyphenol oxidase (PPO). The statistical design was completely randomized with two treatments (purple and yellow onion) with six repetitions. The purple onion presented levels of soluble solids, flavonoids and anthocyanins, more significant than the white onion. Both onions showed enzymatic activity, without significant differences.